Analisis Isi Pesan Religius Pada Tayangan Opening Ceremonial Fifa World Cup Qatar 2022 - Habibullah Habibullah; Tessa Shasrini (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The opening ceremony of Qatar 2022 world cup starting at 9:00 pm is broadcasted exclusively live streaming via video. The Qatar 2022 World Cup opening ceremony was held at AL-Bayt Stadium, with a capacity of 60,000. Being an interesting spectacle for the community. With Roland Barthes' semiotic theory, there are three sides of meaning that need to be studied from an expression, namely denotation meaning, which is a concrete sense of connotation meaning, which means with subjective and emotional elements and finally mythical meaning to determine the content analysis of religious messages. This research is to find out how the content analysis of religious messages on the opening ceremonial broadcast of the FIFA World Cup Qatar 2022. This research uses descriptive qualitative with data analysis techniques in the form of observation and documentation. The results showed that typographically, the Opening Ceremonial of FIFA World Cup Qatar 2022 by providing information about the religious message to be conveyed. There are several contents of religious messages in the Fifa World Cup Qatar 2022 Opening Ceremonial broadcast, namely peace, unity in diversity and conveying messages of humanity, tolerance and unity between nations. This broadcast invites following the Commandments of the Quran such as not drinking beer or women dressing sexy and conveying messages of humanity, tolerance and unity between nations. Eastern society uses robes not as a means of worship, but also in daily life.